PEMBERDAYAAN UMKM ILHAM LAUNDRY MELALUI PENDAMPINGAN PROMOSI DIGITAL DAN PENGELOLAAN USAHA - Nora Listiana; Nur Fitri Dewi; Sri Anawati; Febria Anjara; Aulia Choiri Windari; Suci Ayu Sudari; Alfi Maghfuriyah; Yuni Pambreni (Pengabdian Masyarakat Ilmu Pendidikan, 2026)
This Community Service activity aims to analyze and assist the development of the Ilham Laundry MSME, located near the University of Indonesia. Methods used included direct observation, interviews with the business owner, and simple mentoring on promotion and business management. The results of the activity indicate that Ilham Laundry has been able to survive the competition and challenges of the pandemic through quality service and the use of digital technologies, such as WhatsApp Business and Google Maps. This Community Service activity contributes to improving the understanding of MSME business strategies and supporting the sustainability of laundry services in a more adaptive and competitive manner.